Síntese e caracterização de TiO2 com modificações superficiais para aplicação em fotocatálise heterogênea - Santos, Lidiaine Maria dos (2017)
This study involved the synthesis of photocatalysts by a modified sol-gel method employing different glycols, which are heat-treated in oven muffle type or by a hydrothermal condition. In a second stage of this study it was analyzed the influence of the time of hydrothermal treatment on the structural and optical properties of the photocatalysts synthesized using ethylene glycol. The photocatalytic activity of these oxides was evaluated by degradation of the Ponceau 4R dye (P4R), showing that the oxide synthesized in the presence of ethylene glycol, with hydrothermal thermal treatment for 8h (TiÜ2G1HT8) presented the best performance. This oxide had its surface modified by the incorporation of copper in the form of copper nitrate, followed by photoreduction, resulting in materials with three different nominal concentrations of metallic copper: 0.5, 2.0 and 5.0%. For the purpose of investigating the structural, morphological and electronic changes in the synthesized compounds, different techniques of characterization were employed, including transmission electron microscopy (TEM), X-ray diffraction (XRD), specific surface area (BET), absorption spectroscopy in the ultraviolet and visible, and Raman spectroscopy. The MET analyses showed that oxides submitted to hydrothermal treatment feature spherical morphology, being formed by partially aggregated particles with sizes varying between 2 and 5 nm. According to the analysis by X-rays diffraction, anatase crystalline phase was prevalent in all the synthesized compounds, with presence of brookite phase for samples that received hydrothermal treatment, or were synthesized under the presence of polyethylene glycol, with heat treatment in muffle oven. The amount of brookite as well as the cell volume, deformation, network parameters and crystallinity, was estimated by Rietveld refinement. The surface area and porosity of the material were higher when the synthesis involved the use of hydrothermal treatment, despite the surface modifications, the mesoporosity was maintained, with mean pore diameter between 47 - 56 Â. Raman spectroscopy data of some samples, mainly the synthesized under hydrothermal treatment, suggest the existence of anatase and active modes of broquita in the structure, confirming the results of XRD. The best photocatalytic performance in laboratory scale (90% of mineralization of P4R dye) was achieved with the use of TiÜ2G1HT8 oxide impregnated with 5.0% copper (Cu5.0%/TiÜ2). In solar photocatalysis, the catalyst TiÜ2G1HT8 reached 100% and 66% of discoloration and mineralization of the P4R dye, with the application in all cases of a cumulative dose of UVA equal to 600 kJ m-2, equivalent to 6 hours of exposure in Uberlândia, MG, in the autumn.